A strategic method for steering a photovoltaic generator ISSN / ISBN 2308-4375 / 978-1-61208-620-0 - Bouhafna Khyreddine (eKNOW 2018 : The Tenth International Conference on Information, Process, and Knowledge Management 25-29 March Rome, Italy, 2018)
T There are several forms of electricity generation, first, by burning fuels, such as coal, natural gas or oil, which have an effect on the atmosphere, especially increasing greenhouse gases, or, second, from renewable sources, such as wind, hydro and solar, which are clean and renewable sources of energy. Our work focuses on solar sources, especially photovoltaics; we have treated the steering part of photovoltaic generators using artificial intelligence methods, specifically, case-based reasoning. The system we have built generates actions to be applied to the generator based on its current state and reasoning from previous cases recorded in the case base.